2021
DOI: 10.12911/22998993/140262
|View full text |Cite
|
Sign up to set email alerts
|

Response of Chive (<i>Allium schoenoprasum</i> L.) Plant to Natural Fertilizers

Abstract: Chives (Allium schoenoprasum L.) is a perennial plant [Singh et al., 2018], which was recently introduced to the Egyptian market. It belongs to the Alliaceae family and the Allium genus, which contains many important plants such as garlic, leeks, shallots, and onion [Yoldas et al., 2019]. Because it is has medicinal and edible functions [Jiang-xue et al., 2018], it is widely cultivated around the world. The plant is distinguished in taste and rich in sulfur compounds that can be used for its antimicrobial prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Purple, ball-shaped flowers classify this species as an attractive ornamental plant [42]. Considering their healing effect, many studies have indicated that chives exhibit antioxidant activity [43]. Research by Eisazadeh et al has shown that chives are suitable for phytoremediation, especially for reducing the concentration of cadmium in contaminated soil [44].…”
Section: A Schoenoprasum-chivesmentioning
confidence: 99%
“…Purple, ball-shaped flowers classify this species as an attractive ornamental plant [42]. Considering their healing effect, many studies have indicated that chives exhibit antioxidant activity [43]. Research by Eisazadeh et al has shown that chives are suitable for phytoremediation, especially for reducing the concentration of cadmium in contaminated soil [44].…”
Section: A Schoenoprasum-chivesmentioning
confidence: 99%